2015
DOI: 10.1108/scm-12-2013-0487
|View full text |Cite
|
Sign up to set email alerts
|

Product architecture and supply chain design: a systematic review and research agenda

Abstract: Purpose – The purpose of this paper is to systematically review the extant literature on the relationship between product architectures and supply chain design to identify gaps in the literature and identify future research opportunities. Design/methodology/approach – This paper examines the peer-reviewed literature on product architectures and supply chain written in English. The search strategy is based on selected databases and keywor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 80 publications
1
49
0
Order By: Relevance
“…Pashaei and Olhager [13] conducted a systematic review of the extant literature on the relationship between product architectures and supply chain design. They identified a major research gap concerning limited research on the management of risks associated with product architectures and supply chain design.…”
Section: Risks In New Product Developmentmentioning
confidence: 99%
“…Pashaei and Olhager [13] conducted a systematic review of the extant literature on the relationship between product architectures and supply chain design. They identified a major research gap concerning limited research on the management of risks associated with product architectures and supply chain design.…”
Section: Risks In New Product Developmentmentioning
confidence: 99%
“…While many firms are convinced of aligning their product offerings with customer requirements, these decisions tend to create a number of challenges to the performance of their operations (Salvador, Forza, and Rungtusanatham 2002). The management of the relationship between products, and specifically product architecture (PA) and global operations networks (GON) is important but not straightforward (Pashaei and Olhager 2015). Product architecture decisions are relevant for both the operational performance and product performance (Fixson and Park 2008) and it has commonly been suggested that the structure of the products should mirror its organization (Colfer 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A large body of literature indicates the need to consider supply chain designs in addition to product and process designs in NPD (Pashaei and Olhager, 2015, Nepal et al, 2012, Petersen et al, 2005, Wang et al, 2018. Involving suppliers and customers in NPD has been viewed as an important approach for a manufacturer to obtain external resources and knowledge (e.g., Lau, 2011b, Salvador and Villena, 2013, Peng et al, 2014.…”
Section: Introductionmentioning
confidence: 99%